2017
DOI: 10.5219/695
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols content and antioxidant activity of paprika and pepper spices

Abstract: Paprika spices (Capsicium annuum) and black pepper spices (Piper nigrum) are very popular seasonings for culinary and industrial utilization due to the change of sensory quality (taste, aroma, color) of foods and meals with their addition; their health promoting properties; and also, relevant antioxidant activity. Polyphenols are often responsible for the antioxidant capacity of plant products therefore in our study the content of polyphenols (TP) and antioxidant activity (TAA) were assessed in two common culi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Peppers are an excellent source of antioxidants such as flavonoids, capsaicinoids, vitamin C and carotenoids (Russo, 2012;Škrovánková et al, 2017). In comparison with other species of vegetable, peppers are among those with the highest antioxidant activity (Halvorsen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Peppers are an excellent source of antioxidants such as flavonoids, capsaicinoids, vitamin C and carotenoids (Russo, 2012;Škrovánková et al, 2017). In comparison with other species of vegetable, peppers are among those with the highest antioxidant activity (Halvorsen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the samples stored at 4°C showed a high level of phenolic content due to the leaching mechanism (PC: 1.69 ± 0.24‒0th day to 2.44 ± 0.02‒12th day; FC: 0.045 ± 0.001‒0th day to 0.019 ± 0.01‒12th day). Škrovánková et al (2017) documented that C. annuum sample had a high amount of phenolic compounds compared to flavonoid content (Škrovánková et al., 2017). Taken together, it could be suggested that there is no positive effect in withstanding the phytoconstituent levels with NaOCl treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The total polyphenols of analyzed paprika spices ranged from 14.67 mg/GAE. 19 The color stainability in paprika is because of the presence of polyphenols and the pigments such as capsanthin, capsorubin, and β-carotene. The present study shows that paprika stains less when compared to turmeric and saffron, owing to its less polyphenolic content.…”
Section: Discussionmentioning
confidence: 99%